Avaliação química e farmacológica do óleo destilado de copaiba (Copaifera spp. - LeguminosaeCaesalpinoideae) e aplicações biotecnológicas - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The crude oil-resin (OBC) of Copaifera (Copaifera spp.) has been used by Amazonian populations for the treatment of inflammation, wound healing, bronchitis and skin ulcers. OBC obtained from different species has differences in its chemical composition, making difficult to standardize its use in the pharmaceutical and cosmetic industry. However, the volatile fraction of OBC could be a viable alternative for the standardization because, even from different species, it presents a more homogeneous composition. The objective of this study was to evaluate the physicochemical, chemical composition and the toxic-pharmacological activity of the ODC and the nanoemulsion prepared with this oil. ODC was obtained by steam distillation. Its organoleptic properties, physical properties (aspect, density, and pH) and the chemical composition by GC/MS were evaluated. Subsequently, the nanoemulsion containing 15% of ODC (NE15%) was developed. The anti-inflammatory and antiarthritic activity, the acute oral toxicity and cytotoxicity of the ODC and nanoemulsion were evaluated. The ODC contains 14 sesquiterpenes in its composition, being β-caryophyllene (40.7%) the most abundant. NE15% presented a particle size of 99.47 nm, a polydispersity index of 0.224, and a zeta potential of -37.10 mV. The nanoemulsion showed stability on shelf conditions for up to 180 days. NE15% presented an inhibition on the production of NO higher than the ODC, and potent anti-nociceptive activity in mice at a dose of 100 mg/kg, which was similar to indomethacin and morphine. ODC and OBC showed antiulcerogenic activity in rats in gastric lesions induced by ethanol (doses of 10 and 400 mg/kg). NE15% showed an anti-inflammatory activity similar to dexamethasone and higher than the ODC (ear edema test, in mice) and produced a potent antiarthritic effect that was superior to the ODC and OBC. Both nanoemulsion and ODC showed neither cytotoxicity against non-neoplastic human lung fibroblasts (MRC-5), nor acute toxicity at the maximum dose of 2000 mg/kg in Balb C mice. The results of this study may allow the introduction of the ODC as raw material for industry and the use of the NE15% as an active ingredient in finished pharmaceutical forms, which could be used in the anti-inflammatory therapy.
Keywords: Copaíba; Essências e óleos essenciais; Agentes antiinflamatórios; CIÊNCIAS DA SAÚDE: FARMÁCIA; Copaíba; b-cariofileno; Nanoemulsão; Atividade anti-nociceptiva; Atividade antiedematogênica; Atividade antiartrítica; Atividade anti-ulcerogênica